Analisis Stabilitas Timbunan Tanah dengan Perkuatan Dinding Penahan dan Geotextile - Dandel, Randy; Sendow, Theo K.; Sangkertadi , Sangkertadi (CV. Green Publisher Indonesia, 2025)
Based on finite element analysis using Plaxis 2D version 8.6 for the Retaining Wall Construction Project at PT. Ganda Alam Makmur, this research quantitatively proves that the combination of cantilever retaining walls and woven geotextile significantly increases the safety factor (Msf) of soil embankments from 1.542 (without geotextile, height 7 m) to 4.994 (with 3 layers of geotextile), exceeding the minimum requirements of SNI 8460:2017 (Msf ≥ 1.5). The installation of geotextile also reduces total settlement (U_total) from 0.816 m to 0.347 m at an embankment height of 7 m through the mechanism of uniform load distribution and soil confinement. Under operational loading of double-trailer vehicles, this reinforcement system maintains an Msf of 3.143 with a controlled U_total of 0.306 m, which is classified as acceptable settlement according to geotechnical standards. The analysis results show that the combination of cantilever retaining walls and woven geotextile effectively increases the safety factor, controls structural deformation, and reduces subsoil settlement under the embankment. The stability enhancement mechanism occurs through the role of geotextile in resisting tensile stress, distributing loads evenly, confining soil, and reducing stress concentrations in critical structural zones. This research provides an efficient and economical engineering solution for soil embankment reinforcement.